DESAIN ULANG PEKERJAAN, PERSEPSI KEGUNAAN TEKNOLOGI DAN PRODUKTIVITAS KERJA ASESOR BAN S/M PROVINSI BENGKULU SELAMA COVID-19 - Ahmad Tsaqofi; Intan Zoraya (UNIB Press, 2025)
The objective of this research is to find out the describe of work redesign, technology and assessor job productivity in the Bengkulu Province during Covid-19 Pandemic. This research was used descriptive quantitative research. The data were obtained through the questionnaire’s distribution. The respondents were 25 peoples of assessors, taken by census techniques. Data analysis methods was used descriptive analysis. Based on field research, the results were: (1) The redesign of work carried out by BAN school/madrasah assessors in Bengkulu Province has supported the achievement of work productivity of school/madrasah assessors in Bengkulu Province. This result indicates that the better the redesign of the work carried out, it will have a positive impact on the work productivity of school/madrasah assessors in Bengkulu Province, especially during the COVID-19 pandemic and (2) The perceived usefulness has supported the achievement of work productivity of school/madrasah assessors in Bengkulu Province, especially during the COVID-19 pandemic. This result indicates that the better the technology used, it will have a positive impact on the work productivity of school/madrasah assessors in Bengkulu Province.